Extracorporeal Antioxidant Therapy in Gynecological Cancer Patients - S. V. Tumanyan; L. G. Ivanova (Общая реаниматология, 2008)
Objective: to improve the quality of anesthetic maintenance in gynecological cancer patients, by using extracorporeal antioxidant pharmacotherapy with cytoflavin. Subjects and methods: studies were conducted in 68 patients surgically treated for gynecological cancer. They performed 24 hours before surgery, in the traumatic state of an operation, and within 24 postoperative hours. The parameters of lipid peroxidation and antioxidant system were estimated. The levels of malonic dialdehyde and dienic conjugates and the activities of superoxide dismutase, catalase, and cerulo-plasmin in the red blood cells and plasma, as well as the concentrations of vitamins A and E were determined. At these stages, differential blood counts were estimated to determine the development of adaptive reactions and the exposure to stress. Results: the performed studies demonstrated that the use of cytoflavin as a component of an anesthetic appliance in different surgical stages promoted the elimination of damaging factors resulting from the activation of free radical oxidation and its administration into patients’ autoblood could enhance the efficiency of this agent and reduce the time of development of adaptive processes. Conclusion. The findings show it necessary to use antioxidants that are able to protect the body at the stages of surgical treatment and anesthesia. Key words: oxidative stress, extracorporeal antioxidant correction.